Pengaruh Electronic Word Of Mouth, Kualitas Produk Dan Persepsi Harga Terhadap Keputusan Pembelian Di Ayam Woku Dapoer Ceisya Jakarta Timur - Elfenia, Elfenia Haqqu Aurel; Cyasmoro, Verry (Indonesian Journal Publisher, 2025)
The purpose of this study is to examine how pricing perception, product quality, and Electronic Word of Mouth (e-WOM) affect decisions to buy at Ayam Woku Dapoer Ceisya in East Jakarta. This study employs a survey methodology and a quantitative approach, gathering primary data from 100 participants via online questionnaires disseminated via Google Forms. Accidental sampling is the method of sampling that is employed. “The F-test, coefficient of determination (R2), t-test, multiple linear regression analysis, and classical assumption tests were performed in SPSS. The study found that product quality and pricing perceptions positively and significantly affect buying decisions. No e-WOM impact was seen. The F-test shows that price perception, product quality, and e-WOM influence simultaneous purchases”. The coefficient of determination (R2) of 0.786 shows that these three factors explain 78.6% of purchasing decisions. This study offers factual proof that consumers' perceptions of product quality and pricing are important factors when making judgments about what to buy in the culinary sector.